a c , a a b c , a a a b b c , a a a a b b b c , …
Find all triples of integers ( a , b , c ) such that 0 < a , b , c < 1 0 and all of the terms in the above sequence are square numbers.
If those triples are ( a 1 , b 1 , c 1 ) , ( a 2 , b 2 , c 2 ) , … , ( a n , b n , c n ) with a 1 ≤ a 2 ≤ ⋯ ≤ a n , write your answer as a 1 b 1 c 1 a 2 b 2 c 2 … a n b n c n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just searched for cases ac,aabc using M a t h e m a t i c a
Select[Tuples[Range@9,{3}],IntegerQ@Sqrt[FromDigits@{#,#3}&@@#]&&IntegerQ@Sqrt[FromDigits@{#,#,#2,#3}&@@#]&]
and got the right answer
{{1, 5, 6}, {4, 8, 9}}
How does this show that all the numbers in both the sequences { 1 6 , 1 1 5 6 , 1 1 1 5 5 6 , 1 1 1 1 5 5 5 6 , … } and { 4 9 , 4 4 8 9 , 4 4 4 8 8 9 , 4 4 4 4 8 8 8 9 , … } are perfect squares?
Log in to reply
This is how I got the right answer. It is not a proof. When you are brute-forcing a problem like this with a computer you test as less test cases as you can. Did you solve it? Please share your thoughts on this problem
Log in to reply
No. I don't know how to prove that ( a , b , c ) = ( 1 , 5 , 6 ) , ( 4 , 8 , 9 ) must be true.
Problem Loading...
Note Loading...
Set Loading...
let N m = m times a a ⋯ a m-1 times b b ⋯ b c
Then, using that y times 1 1 ⋯ 1 = 9 1 0 y − 1
N m = a × 1 0 m × 9 1 0 m − 1 + b × 1 0 × 9 1 0 m − 1 − 1 + c
If x = 1 0 m
N m = 9 x 2 − x × a + 9 x − 1 0 × b + c
We will assume that N m = u 2 with u an integer
u 2 = 9 x 2 − x × a + 9 x − 1 0 × b + c ( 3 u ) 2 = ( a ) x 2 + ( b − a ) x + 9 c − 1 0 b
The above equation is cuadratic, and if it is a perfect square, then, the discriminant is equal to 0
( b − a ) 2 − 4 ( a ) ( 9 c − 1 0 b ) = 0 b 2 − 2 a b + a 2 − 3 6 a c + 4 0 a b = 0 b 2 + 2 a b + a 2 − 3 6 a c + 4 0 a b = 4 a b ( a + b ) 2 = 3 6 a c − 3 6 a b ( a + b ) 2 = 3 6 a ( c − b )
We get that
6 ∣ ( a + b ) , b < c and a ∣ b
Trying values for a give us all the triplets: ( 1 , 5 , 9 ) and ( 4 , 8 , 9 )